Bibliometric analysis of biologic treatments for chronic rhinosinusitis - Huang, Yue; Chen, Yulan; Li, Qihong; Sui, Wen; Pan, Zhuo; Yang, Hao; Lv, Zeyi; Chen, Xi; Yin, Man; Li, Yu; Li, Xinrong (Frontiers in Medicine, 2025)
BackgroundChronic rhinosinusitis (CRS) significantly impacts patients’ quality of life. The use of biologic therapies in CRS management has gained traction in clinical practice. However, no bibliometric analysis has been conducted in this area thus far. This study aims to provide a comprehensive overview of the knowledge framework and research trends regarding biologic treatments for CRS.MethodsA bibliometric analysis was performed on 888 publications related to biologic treatments for CRS, published between 2011 and 2024. Literature was retrieved from the Web of Science (WoS), and data visualization and trend analysis were conducted using VOSviewer, CiteSpace, and Bibliometrix software tools.ResultsResearch on biologic therapies for CRS peaked in the past 6 years. Key contributors include Claus Bachert, the United States, and the University of Ghent. The most cited article is “Efficacy and safety of dupilumab in patients with severe chronic rhinosinusitis with nasal polyps (LIBERTY NP SINUS-24 and LIBERTY NP SINUS-52): results from two multicenter, randomized, double-blind, placebo-controlled, parallel-group phase 3 trials.” The five most explosive keywords are: expression (5.03), placebo-controlled trial (3.68), anti-IgE (3.35), anti-IgE antibody (3.22), and phenotypes (4.55). Current research on biologic treatments for CRS predominantly focuses on clinical applications.ConclusionThis study offers a bibliometric visualization of the literature on biologic treatments for CRS, highlighting key developments and emerging research trends in the field. It provides valuable references for scholars and outlines future research directions to further advance the field.